Applying Prunckun’s Intelligence Strategy Model in Counter-Radicalism and Terrorism Efforts in Indonesia: A Defensive–Offensive Approach - Prawira, Bagus Yudha (Security Intelligence Terrorism Journal (SITJ), 2025)
Radicalism and terrorism pose a clear threat to Indonesia’s national security, impacting not only the political domain but also the country’s social cohesion, economic stability, and national integrity. This paper discusses intelligence strategies to counter these threats through defensive and offensive approaches. The defensive strategy involves preventive measures against the spread of radical ideologies, recruitment efforts, and the implementation of deradicalization programs. In contrast, the offensive strategy involves the disinformation efforts, the capture of key figures, and the disruption of financial resources. Drawing on Henry Prunckun’s holistic intelligence strategy model (2014), this paper highlights the importance of synergy between domestic agencies and international cooperation in safeguarding national stability. Through a comprehensive approach, intelligence strategies can serve as the front line in confronting the threat of radical terrorism.